2020
DOI: 10.1098/rsbl.2020.0094
|View full text |Cite
|
Sign up to set email alerts
|

Experience shapes accuracy in territorial decision-making in a poison frog

Abstract: The trade-off between speed and accuracy affects many behavioural processes like predator avoidance, foraging and nest-site selection, but little is known about this trade-off relative to territorial behaviour. Some poison frogs are highly territorial and fiercely repel calling male intruders. However, attacks need to be conducted cautiously, as they are energetically costly and bear the risk of own injury or accidentally targeting the wrong individual. In this study, we investigated the speed–accuracy trade-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…For each model, we included the SPL, but also the trial number, and the individual size as fixed effects, to account for habituation and effect of body size on aggressive responses. Previous studies have shown that age influences the accuracy of aggressive responses in A. femoralis, and that body size is positively correlated to age (Ursprung et al, 2011b;Sonnleitner et al, 2020). In all models ID was included as random effect to account for repeated measurements.…”
Section: Discussionmentioning
confidence: 99%
“…For each model, we included the SPL, but also the trial number, and the individual size as fixed effects, to account for habituation and effect of body size on aggressive responses. Previous studies have shown that age influences the accuracy of aggressive responses in A. femoralis, and that body size is positively correlated to age (Ursprung et al, 2011b;Sonnleitner et al, 2020). In all models ID was included as random effect to account for repeated measurements.…”
Section: Discussionmentioning
confidence: 99%
“…femoralis males, playbacks alone may be enough to provoke a phonotactic reaction followed by an androgen response, but the intensity of phonotactic approach may depend on the combination of acoustic and visual signals (see also Sonnleitner et al 2020). Further experiments on the hormonal and behavioural response to territorial intrusions in territorial frogs may profit from the combination of playbacks and robotic frog models in order to create more realistic situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although A. femoralis males are strongly territorial and usually males jump towards the sound source in playback experiments (Hödl, 1983), they require to be confronted by bimodal signals (acoustic and visual) in order to display physical attacks (Narins et al, 2003). Thus, in A. femoralis males, playbacks alone may be enough to provoke a phonotactic reaction followed by an androgen response, but the intensity of phonotactic approach may depend on the combination of acoustic and visual signals (see also Sonnleitner et al 2020). Further experiments on the hormonal and behavioural response to territorial intrusions in territorial frogs may profit from the combination of playbacks and robotic frog models in order to create more realistic situations.…”
Section: Discussionmentioning
confidence: 99%
“…Territory holders typically respond to calling intruders by orientating their head/body and jumping towards the intruder. If an intruder does not retreat and continues calling, the territory holder might escalate the conflict and start wrestling with the intruder 26 , 42 , 44 – 46 . We used a loudspeaker with an integrated music player (MUVO 2c, Creative, Singapore) for playbacks.…”
Section: Methodsmentioning
confidence: 99%